Nanoparticles Toxicity in Fish Models - Cazenave, Jimena; Ale, Analía; Bacchetta, Carla; Rossi, Andrea S. (Current Pharmaceutical Design, 2019)
The increasing production and use of nanoparticles (NP) have raised concerns regarding the potential toxicity to human and environmental health. In this review, we address the up to date information on nanotoxicity using fish as models. Firstly, we carried out a systematic literature search (articles published up to February 2019 in the Scopus database) in order to quantitatively assess the scientific research on nanoparticles, nanotoxicity and fish. Next, we carried out a narrative synthesis on the main factors and mechanisms involved in NP toxicity in fish. According to the bibliometric analysis, there is a low contribution of scientific research on nanotoxicity compared with the general nanoparticles scientific production. The literature search also showed that silver and titanium NP are the most studied nanomaterials and Danio rerio is the fish species most used. In comparison with freshwater fish, the effects of nanomaterials on marine fish have been little studied. After a non-systematic literature analysis, we identified several factors involved in nanotoxicity, as well as the effects and main toxicity mechanisms of NP on fish. Finally, we highlighted the knowledge gaps and the need for future research.
Keywords: Nanoecotoxicology